Zooplankton dynamics and pesticide influence in a stream basin affected by land use change in the Argentine Espinal region - Van Opstal, Natalia Veronica (2026)
Watercourses in agricultural areas often receive diffuse pesticide inputs through drift, runoff, infiltration, and erosion. We assessed the qualitative and quantitative response of the zooplankton community to pesticide exposure in the Estacas stream basin, Argentina, over two years at seven sites. Surface water and zooplankton were sampled every two months, and 125 pesticides were screened and classified by detection frequency. A total of 24 pesticides and the AMPA metabolite were detected. Dominant pesticides included atrazine, glyphosate, and AMPA in the first year, and metolachlor and S-metolachlor in the second. Sixty-three zooplankton taxa were identified, primarily rotifers (65%) and cladocerans (35%), with peak richness at one site during spring of the second year. Copepods were present but less frequent, with Cyclopoida being the most common. Microzooplankton dominated across sites, with higher densities in the first year. Canonical Correlation Analysis showed that glyphosate and atrazine were probably associated with microzooplankton abundance in the first year, while metolachlor and S-metolachlor were associated with copepod and rotifer populations in the second. This study represents the first report on zooplankton community responses to pesticide gradients in this basin, providing crucial information on this bioindicator’s sensitivity to land use changes and pesticide application timing. These insights can help the development of environmentally sustainable agricultural practices.